Ixodes ricinus ticks are reservoir hosts for Rickettsia helvetica and potentially carry flea-borne Rickettsia species - Gaasenbeek Cor; Borgsteede Fred; Brandenburg Afke H; Reusken Chantal; Fonville Manoj; Wielinga Peter R; Sprong Hein; van der Giessen Joke WB (Parasites & Vectors, 2009)
Abstract Background Hard ticks have been identified as important vectors of rickettsiae causing the spotted fever syndrome. Tick-borne rickettsiae are considered to be emerging, but only limited data are available about their presence in Western Europe, their natural life cycle and their reservoir hosts. Ixodes ricinus, the most prevalent tick species, were collected and tested from different vegetation types and from potential reservoir hosts. In one biotope area, the annual and seasonal variability of rickettsiae infections of the different tick stages were determined for 9 years. Results The DNA of the human pathogen R. conorii as well as R. helvetica, R. sp. IRS and R. bellii-like were found. Unexpectedly, the DNA of the highly pathogenic R. typhi and R. prowazekii and 4 other uncharacterized Rickettsia spp. related to the typhus group were also detected in I. ricinus. The presence of R. helvetica in fleas isolated from small rodents supported our hypothesis that cross-infection can occur under natural conditions, since R. typhi/prowazekii and R. helvetica as well as their vectors share rodents as reservoir hosts. In one biotope, the infection rate with R. helvetica was ~66% for 9 years, and was comparable between larvae, nymphs, and adults. Larvae caught by flagging generally have not yet taken a blood meal from a vertebrate host. The simplest explanation for the comparable prevalence of R. helvetica between the defined tick stages is, that R. helvetica is vertically transmitted through the next generation with high efficiency. The DNA of R. helvetica was also present in whole blood from mice, deer and wild boar. Conclusion Besides R. helvetica, unexpected rickettsiae are found in I. ricinus ticks. We propose that I. ricinus is a major reservoir host for R. helvetica, and that vertebrate hosts play important roles in the further geographical dispersion of rickettsiae.